2019
DOI: 10.1016/j.jare.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Determination of excitation temperature in laser-induced plasmas using columnar density Saha-Boltzmann plot

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The electron density has been calculated from the Hα line at 656.27 nm using LIBS ++ software. 41 Hydrogen emission comes from the air surrounding the plasma, where the electron density measurements from the Hα line are free from self-absorption. 42 The electron density values were more than 10 16 under the selected parameters, which verify LTE’s McWhirter criterion in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The electron density has been calculated from the Hα line at 656.27 nm using LIBS ++ software. 41 Hydrogen emission comes from the air surrounding the plasma, where the electron density measurements from the Hα line are free from self-absorption. 42 The electron density values were more than 10 16 under the selected parameters, which verify LTE’s McWhirter criterion in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature of generated plasma was determined using an accurate and simple procedure known as Boltzmann plot [22,27]. The plasma temperature was estimated by including the optically thin spectral lines with spectroscopic data from NIST database.…”
Section: Measurement Of Plasma Temperaturementioning
confidence: 99%
“…The method parameters depend on laser irradiance, wavelength, pulse duration, target material, atmospheric conditions, space, and time. Different studies have shown that using an optically thin LIBS, the excitation temperature that controls the distribution of energy level excitation can be determined by Boltzmann equation [22,23], while the ionization temperature can be estimated by ionization equilibrium calculations using Saha equation which is known as plasma [24,25]. In the present work, tests were conducted to determine major and trace elements of an important medicinal plant ZA collected from the district Bagh, Azad Jammu and Kashmir, Pakistan.…”
Section: Introductionmentioning
confidence: 96%
“…A precise calculation of the plasma electron temperature is important for the quantitative study of the plasma composition. While many spectroscopic techniques are required for the calculation of the excitation temperatures in LIBS, the Saha-Boltzmann plot method is the most popular (Safi et al, 2019). There is an underlying implicit constraint in the Saha-Boltzmann plot approach.…”
Section: Calculation Of Electron Densitymentioning
confidence: 99%